2020
DOI: 10.1017/s003118202000164x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Angiostrongylus cantonensis infection in definitive and intermediate hosts in Hawaii, a global hotspot of rat lungworm disease

Abstract: Angiostrongylus cantonensis (rat lungworm) is a tropical and subtropical parasitic nematode, with infections in humans causing angiostrongyliasis (rat lungworm disease), characterized by eosinophilic meningitis. Hawaii has been identified as a global hotspot of infection, with recent reports of high infection rates in humans, as well as rat definitive and snail intermediate hosts. This study investigated variation in A. cantonensis infection, both prevalence and intensity, in wild populations of two species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The significance of tibia length as a predictor in our model supports the concept that older rats are more likely to have been exposed to the parasite at some point during their lifespan, possibly even multiple times ( Simões et al, 2014 ; Niebuhr et al, 2021 ). This contrasts with Jarvi et al (2017) , who reported a negative correlation between weight (another proxy for age) and adult worm burden in Hawaiian R. rattus .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The significance of tibia length as a predictor in our model supports the concept that older rats are more likely to have been exposed to the parasite at some point during their lifespan, possibly even multiple times ( Simões et al, 2014 ; Niebuhr et al, 2021 ). This contrasts with Jarvi et al (2017) , who reported a negative correlation between weight (another proxy for age) and adult worm burden in Hawaiian R. rattus .…”
Section: Discussionsupporting
confidence: 76%
“…Our previous work at a zoo in western Sydney (approximately 30 km west of the city of Sydney) demonstrated that 9/14 (64%) of trapped R. norvegicus were infected with A. cantonensis ( Rivory et al, 2023 ). The prevalence in the present study is considerably lower, highlighting the random variation in A. cantonensis abundance between complex host-parasite systems from one habitat to another ( Niebuhr et al, 2021 ; Rollins et al, 2021 ).…”
Section: Discussionmentioning
confidence: 47%
“…This Special Issue of Parasitology is based on cutting-edge research presented at the 6th International Workshop on Angiostrongylus and Angiostrongyliasis held in Hilo, Hawai`i, in January 2020. It provides research updates on gastropod and rat infection levels under natural conditions in multiple geographic areas (Niebuhr et al, 2021;Estano et al, 2021;Walden et al, 2021), under laboratory conditions (Hamilton et al, 2021;Wun et al, 2021a, b), as well as alternative parasite transmission pathways (Modry et al, 2021). The latest research on infection in non-human species is described (Feckova et al, 2021;Malik et al, 2021;Tsai and Chen, 2021;Wun et al, 2021a, b).…”
Section: Long-term Sequelaementioning
confidence: 99%
“…Metastrongyloidea (Nematoda: Strongylida), also known as lungworms or metastrongyles, are common parasites of the respiratory, cardiovascular and rarely the auditory system of mammals (Measures, 2001 ). The definitive hosts become infected through ingestion of larval stages within invertebrate intermediate hosts or free on pasture; therefore, metastrongyle infection can be quite common among free-foraging domestic and wild mammals (Measures, 2001 ; Regassa et al ., 2010 ; Niebuhr et al ., 2021 ). Like other helminth infections, the pathogenic effects of metastrongyloidiasis can be broad with impacts that range from subclinical infection to bronchopneumonia and death (Measures, 2001 ; Forbes, 2021 ).…”
Section: Introductionmentioning
confidence: 99%